International grain markets: Russia as a new power? - Thomas Glauben; Zsombor Pàll; Oleksandr Perekhozhuk; Sören Prehn; Ramona Teuber (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2012)
Russia, a former net importer of wheat, has developed into one of the leading actors in the world wheat market within the last decade. Forecasts suggest that Russia's share in the world market may increase even further and Russia might become the world's largest wheat exporter by 2020. One key research question resulting from this development is whether Russia could use its newly-gained market position in order to exercise market power or price discrimination. This issue could be of particular significance for countries in Central Asia and the Caucasus where Russia - due to their geographical location - is facing hardly any competition. This Policy Brief analyses if and in which countries Russian wheat exporters exercise market power. – – Russland, einstiger Nettoimporteur von Weizen, hat sich innerhalb des letzten Jahrzehnts zu einem der führenden Akteure auf dem Weltweizenmarkt entwickelt. Laut Prognose könnte Russlands Weltmarktanteil sogar noch weiter wachsen und bis 2020 könnte Russland der weltgrößte Weizenexporteur werden. Eine wichtige Frage, die sich hieraus ergibt, ist, ob Russland seine neugewonnene Marktposition dazu nutzen könnte, um Marktmacht bzw. Preisdiskriminierung auszuüben. Insbesondere für die Länder Zentralasiens und des Kaukasus könnte diese Frage von besonderer Bedeutung sein, da sich Russland in diesen Ländern auf Grund ihrer geographischen Lage nur wenigen Konkurrenten gegenüber sieht. Dieser Policy Brief geht der Frage nach, ob und in welchen Ländern russische Weizenexporteure Marktmacht ausüben.
urn:nbn:de:gbv:3:2-32017
Keywords: 330; Weizenmarkt; Getreidemarkt; Welt; Weizen; Export; Marktmacht; Russland